Effect of Management Ownership, Size of Board of Commissioners, Auditor Reputation, Liquidity, Profitability, Leverage on Risk Management Disclosure of Food and Beverage Companies Listed on the Indonesia Stock Exchange (IDX) - Julita Rakhmah Hasibuan; Renny Maisyarah; M. Irsan Nasution (International Journal of Management, Economic and Accounting, 2025)
Adequate risk management disclosure is needed in making the right decisions in the corporate environment. The increasing demand of shareholders for transparent risk disclosure in financial statements has encouraged companies to expand their disclosure areas in annual reports. It is necessary to investigate various factors that can affect risk management disclosure in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2022. Factors that are estimated to affect risk management disclosure are management ownership, board of commissioners size, auditor reputation, liquidity, profitability, and leverage. This study will use multiple regression analysis on data from food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2017 to 2022, to further explore their relationships. The results of the analysis show that all variables in the regression model simultaneously affect the company's risk management disclosure. However, partially among the 6 variables, only 4 variables affect risk management disclosure, namely management ownership, board of commissioners size, auditor reputation, and liquidity. Meanwhile, the profitability and leverage variables are concluded to have no effect. Thus, it can be concluded that only these four factors have an impact on risk management disclosure, so that it can be a concern for shareholders in companies listed on the IDX in the food and beverage category.